A cross sectional study of Net Promoter and its linkage to South African firm growth - Bissict, Gregg Michael (My University, 2012)
This research project undertakes to investigate the linkage between firni Net Promoter score and firm growth in the South African context. South African fmns arc selected from the cellular service provider industry and the retail banking service provider industi7 and a primary research study is undertaken to obtain sample data for the respective firms’ Net Promoter scores. Finn revenue is defined as a suitable measure of firm growth and half year time period from 2010 to 201 1 arc defined as periods from which percentage growth rates may be computed. Revenue data for each linn is collected from public sources and an annual percentage growth rate for each firm is calculated from revenue reported for the first half of 2010 to 2011. A data reliability test is perfonned on the Net Promoter data set and the data is found to be non-uniform and preferential, indicating scores which arc not arbitrary. A Pearson’s correlation analysis is performed to measure the strength of relationship between the Net Promoter scores and percentage firm revenue growth rates. The results of the Pearson correlation analysis indicates a relatively stronger linear relationship between Net Promoter scores and percentage firm revenue growth for the South African cellular service provider industry segment (0.9932) and a relatively weaker linear relationship between that and the South African retail banking industry segment (0.4752). This research finds that there is a positive linkage between Net Promoter scores and revenue growth rates which is consistent with previous research undertaken on the subject.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science in Engineering (Industrial), 2012
Keywords: Consumer satisfaction--South Africa; Marketing research--South Africa; Consumer behavior--South Africa